2021
DOI: 10.3390/toxins13060369
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Gut Microbiota in Acute Kidney Injury

Abstract: Recent studies have revealed that the gut microbiota plays a crucial role in maintaining a healthy, as well as diseased condition. Various organs and systems, including the kidney, are affected by the gut microbiota. While the impacts of the gut microbiota have been reported mainly on chronic kidney disease, acute kidney injury (AKI) is also affected by the intestinal environment. In this review, we discussed the pathogenesis of AKI, highlighting the relation to the gut microbiota. Since there is no establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Current research suggests that the gut microbiota plays an important role in the process leading to the onset and progression of renal diseases ( 8 , 28 ). It has been revealed that gut dysbiosis is closely linked to AKI, and modification of bacterial composition and function might provide treatment options for AKI ( 29 ). According to recent clinical studies, Lactobacillus , Alloprevotella , and Bacteroides were prevalent in patients with kidney injury and positively correlated with biomarkers of AKI, whereas probiotics, including Akkermansia , Faecalibaculum , and Bifidobacterium , were enriched in healthy controls ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current research suggests that the gut microbiota plays an important role in the process leading to the onset and progression of renal diseases ( 8 , 28 ). It has been revealed that gut dysbiosis is closely linked to AKI, and modification of bacterial composition and function might provide treatment options for AKI ( 29 ). According to recent clinical studies, Lactobacillus , Alloprevotella , and Bacteroides were prevalent in patients with kidney injury and positively correlated with biomarkers of AKI, whereas probiotics, including Akkermansia , Faecalibaculum , and Bifidobacterium , were enriched in healthy controls ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In CKD, external factors associated with a specific diet (low fiber intake), longterm antibiotic treatment, phosphate binder treatment, and iron supplementation, and the internal factor of high urea levels modify the gut microbiota and intestinal barrier permeability [ 47 , 48 , 49 , 50 ]. Although AKI and CKD may share common factors, such as a specific diet or the use of antibiotics [ 51 ], a reduction in short-chain fatty acid levels in AKI may play a specific role in the formation of PBUTs by favoring an inflammatory state associated with intestinal barrier disruption [ 13 , 46 , 52 , 53 , 54 , 55 ]. The following sections will focus on the cardiovascular consequences of the main gut-derived PBUTs studied in experimental models of AKI.…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%
“…Such relative variability of observed levels could be explained by several factors, notably a change in the composition of the gut microbiota relative to the patients’ genetic background and clinical setting. Indeed, several factors, such as systemic inflammation, parenteral nutrition, antibiotics, or intestinal permeability, may alter the composition of the gut microbiota [ 51 ]. On the other hand, systemic inflammation and fluid accumulation, resulting in a decrease in serum albumin levels, may also reduce the measured total serum level of IS, particularly in septic AKI.…”
Section: Gut-derived Protein-bound Uremic Toxins and Cardiovascular D...mentioning
confidence: 99%
“…Fecal microbiota transplantation [20] has become a valuable and popular strategy for treating complicated gut diseases associated with gut microbiota disorders. Furthermore, based on 16S rRNA gene sequencing, an enormous amount of research has shown that the composition changes of fecal microbiota are intimately associated with various non-infection and non-infectious diseases of visceral organs; see excellent reviews on various systems and elds [16,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] and new discoveries [35]. According to the explosion of research in this area, gut microbiota have inevitably become the leading cause of many diseases.…”
Section: Cell and Molecular Biology Theory And Technique Progress Hav...mentioning
confidence: 99%